2018
DOI: 10.1016/j.nicl.2018.05.016
|View full text |Cite|
|
Sign up to set email alerts
|

Amyloid pathology fingerprint differentiates post-traumatic stress disorder and traumatic brain injury

Abstract: IntroductionTraumatic brain injury (TBI) and post-traumatic stress disorder (PTSD) are risk factors for early onset of Alzheimer's disease (AD) and may accelerate the progression rate of AD pathology. As amyloid-beta (Aβ) plaques are a hallmark of AD pathology, we hypothesized that TBI and PTSD might increase Aβ accumulation in the brain.MethodsWe examined PET and neuropsychological data from Vietnam War veterans compiled by the US Department of Defense Alzheimer's Disease Neuroimaging Initiative, to examine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 79 publications
4
61
0
Order By: Relevance
“…These brain areas are also known to be the site of the pathophysiological foundations of cognitive impairment caused by the early stages of the disease. Moreover, previous literature found notable accumulations of amyloid in the temporal gyrus in patients who sufferer with significant cognitive dysfunction which suggests partial reason why temporal gyrus is related to cognitive performance (Mohamed et al 2018). In addition, our study showed positive correlations between functional connectivity of insula and temporal gyrus and orientation score.…”
Section: Insula-temporal Connectivitysupporting
confidence: 71%
“…These brain areas are also known to be the site of the pathophysiological foundations of cognitive impairment caused by the early stages of the disease. Moreover, previous literature found notable accumulations of amyloid in the temporal gyrus in patients who sufferer with significant cognitive dysfunction which suggests partial reason why temporal gyrus is related to cognitive performance (Mohamed et al 2018). In addition, our study showed positive correlations between functional connectivity of insula and temporal gyrus and orientation score.…”
Section: Insula-temporal Connectivitysupporting
confidence: 71%
“…These recalled stressful experiences are fairly common, with more than one‐quarter of WTC responders experiencing these symptoms more than a decade after the event [2]. Neuroimaging studies have reported that trauma survivors with chronic PTSD have more rapid hippocampal volume loss [10], reduced cortical thickness [11], increased β ‐amyloid deposition [9], and changes to plasma β ‐amyloid burden [39].…”
Section: Discussionmentioning
confidence: 99%
“…Data acquisition procedures were standardized across all ADNI sites (information can be found at: http://adni.loni.usc.edu/wp-content/uploads/2015/02/01_DOD-ADNI_Tau-Addendum-Protocol_23Oct2014.pdf ). Data were preprocessed and analysed as described in our previous paper [ 25 ] using the FMRIB software library (FSL 5.0.9). MRI images were corrected for intensity inhomogeneity, skull-stripped, and segmented using the RECON-ALL [ 26 ] from Freesurfer.…”
Section: Methodsmentioning
confidence: 99%
“…To assess amyloid positivity, SUV maps of the amyloid [ 18 F]AV45 PET tracer from the same subjects were downloaded. The acquisition parameters were as described previously [ 25 ]. The [ 18 F]AV45 SUV maps were coregistered to individual T1-weighted MR images in native space using FSL-Flirt, and amyloid-PET SUVr values were calculated using the whole cerebellum as the reference region [ 22 ].…”
Section: Methodsmentioning
confidence: 99%